The cognitive impact of the implementation of an entry level certificate in information technology - Van Staden, Corne Johandia (My University, 2013)
Research has found that learners find it difficult to solve programming problems in a logical way, therefore the failure rate in Programming I is high. The Entry-level Certificate in Information Technology was introduced as an intervention to address this problem. Four aspects were focused on in the Entry-level Certificate in Information Technology, namely English comprehension, academic competency, numerical skills and the problem-solving skills of learners. Basic computer literacy was the common theme used throughout the Information Technology Boot Camp (ITBC) to address the above-mentioned aspects, in order to broaden access to the Vaal University of Technology (VUT). The research indicates that English comprehension is a very important component of the Information and Communication Technology (ICT) modules, and that it is important for learners to have an English proficiency level of grade 12 before enroUing for a diploma in I CT. The ICT and numerical skills modules also narrowed the gap between secondary and tertiary education, by equipping the learners with prior knoWJledge that is crucial for being successful in the ICT diploma. To conclude access was broadened to the VUT and the intervention of the ITBC did impact positively on the cognitive functioning of learners.
Thesis (M. Tech.) - Information and Communication Technology, Faculty of Applied and Computer Sciences - Vaal University of Technology
Keywords: Information technology; Programming problems; Entry level certificates; Computer literacy; 004; Information technology